(untitled) (Annual of the Faculty of Philosophy in Skopje, 2015)
Globalization does not equally impact on countries act in different countries with different levels of political, economic and technological development. Its unequal distribution across regions, countries or communities confirms that it is a complex and deep asymmetric process. It was confirmed by numerous theories and debates only to explain and define the phenomenon, but little attention paid to the complexities of globalization and measuring its range. With the help of empirical variables and indicators can measure the differences between national and international in different domains. In that way it allows to be seen to what extent countries are globalized, or be perceived strong influence on globalization processes on the overall situation in societies. Therefore, a larger number of countries are trying to take advantage of the processes of globalization to promote the national interests and the improvement of its position in international relations. Hence the analysis of the indexes of globalization will help us to comprehend with which components of national power countries dominate on the regional and global scene.